HEMOCYTE PROFILE OF SUSUH KURA (Sulcospira Testudinaria) IN ORDER TO EVALUATE THE WATER QUALITY OF BADHER BANK CONSERVATION AREA, TAWANGREJO VILLAGE, BINANGUN DISTRICT, BLITAR - Asus Maizar Suryanto Hertika; Supriatna .; Arief Darmawan; Bimo Aji Nugroho; Agung Dwi Handoko; Agustiansi Yeyen Qurniawatri; Ranita Ayu Prasetyawati (JFMR (Journal of Fisheries and Marine Research), 2021)
Abstract. Badher Bank Conservation Area is a conservation area that is focused on the conservation of badher fish. The purpose of this study was to analyze the hemocyte profile of Susuh Kura (Sulcospira testudinaria) in the Badher Bank Conservation Area and the water quality to estimate pollution status. The research method used is descriptive with survey method. Samples taken are water quality and susah kura samples at 4 stations. Based on the results of water quality measurements obtained results, temperatures of around 27.6-30.7 ° C, current of around 0.6-1 m/s, brightness of around 5-8.5 cm, TSS (Total Suspended Solid) of around 11-46 mg/l, pH of around  7.31-7.58, DO (Dissolved Oxygen) of around 4.4-5.1 mg/l, amoniak of around 0, 0432-0.2143 mg/l, BOD (Biological Oxygen Demand) of around 0.8-2.4 mg /l. These results indicate that all parameters are still in normal conditions except amoniak. THC observation results obtained values between 37.67x104 - 49x104 cells/ml, where the limit of THC values is not more than 58x104 cells/ml.. Analysis on DHC showed that hyalinocytes are around 30.47-40.76%, Semi granulocytes  around 10-15.92% and granulocytes around 44.53-57.84%. Result of CCA show that THC is affected by 8 parameters of moderate concentration, hyalinocytes tend to be influenced by high amoniak and granulocytes tend to be influenced by DO and high brightness. Thus, the condition of the waters in the Badher Bank Conservation Area is still in normal condition.